Diallel analysis in cowpea aiming at selection for extra-earliness - Oliveira,Rosana Mendes de Moura (2016)
Abstract In Brazil, the production of cowpea is concentrated in the Northeast and North; however, in recent years, its cultivation has expanded to the Cerrado biome of the Brazilian Midwest region, where it is incorporated into production arrangements in the form of off-season. In this work, it was carried out a study on the extra-earliness in cowpea in order to select parents and crosses with cycle shorter than 60 days. A test with an F2 generation of a complete diallel cross involving five parents and ten crosses was carried out in a complete randomized block design with six replications. The parents IT82D-889 and AU94-MOB-816 stood out for extra-earliness flowering, while IT82D-60 and IT82D-889 stood out for extra-earliness maturity. The crosses IT82D-60 x AU94-MOB-816 and IT82D-60 x IT82D-889 were more promising in extra-earliness flowering, while IT82D-60 x IT82D-889 and IT82D-60 x MNC04-789B-119-2-3-1 were more promising for extra-earliness maturity.